Electrorheoloical behavior of chitosan dicarboxylate suspensions - Choi, US; Ko, YG (WORLD SCIENTIFIC PUBL CO PTE LTD, 2002)
The electrorheological (ER) behavior of chitosan dicarboxylate suspensions in silicone oil was investigated by varying the electric fields, volume fractions of particles, and shear rates, respectively. The chitosan dicarboxylate susepnsions showed a typical ER response caused by the polarizability of an amide polar group and shear yield stress due to the formation of multiple chains upon application of an electric,field. Of these, chitosan malonicate suspension represented slightly higher rheological performance than any other suspensions due to dependent upon the carbon chain length. The shear stress for the suspension exhibited a linear dependence on an electric field power of 1.88. On the basis of the results, the newly synthesized chitosan dicarboxylate suspensions were found to be an anhydrous ER fluid.